2010
DOI: 10.1002/ajmg.a.33713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hematologic findings in Noonan syndrome patients with PTPN11 gene mutations

Abstract: Reports on Noonan syndrome (NS) have documented multiple types of coagulation defects and bleeding diathesis, and a wide range of clinical presentations. Early studies suggested that a large proportion of NS patients have coagulation defects, whereas more recent reports indicate low rates of coagulopathy. The aim of this study was to evaluate phenotypic characteristics, PTPN11 gene mutations, and hematological and coagulation parameters in 30 clinically diagnosed cases of NS. One of the NS patients had a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The literature review on NS2 4 5 8 reveals multiple types of haemostatic abnormalities attributed to low clotting factor concentrations, in which factor XI is the most frequently described culprit, followed by factor XII and factor VIII.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature review on NS2 4 5 8 reveals multiple types of haemostatic abnormalities attributed to low clotting factor concentrations, in which factor XI is the most frequently described culprit, followed by factor XII and factor VIII.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, periodic clinical and haematologic control should be maintained for several years, especially in patients with somatic mutations in exons 3 and 13 of PTPN11 gene, such as the reported patient 1 2 13 15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that noncoding variants of human HGF cause nonsyndromic hearing loss DFNB39 in many human families (20), and a likely pathogenic variant in MET is associated with DFNB97-linked hearing loss (21). Moreover, deficits of SHP2 and SPRY2 result in hearing loss in humans and mice, respectively (22)(23)(24). Therefore, using real-time PCR and lymphoblastoid cell lines generated from the affected and nonpenetrant individuals of family PK-2, we studied the expression of 37 genes related to HGF signaling ( Figure 8) (25,26).…”
Section: Dfnb26 Allele Effects On the Lipid-binding Ability Of The Gamentioning
confidence: 99%